Academic dishonesty: an empirical study of personal beliefs and values of undergraduate students in Malaysia - Ismail, Suriani; Omar, Zoharah (Universiti Putra Malaysia Press, 2017)
The relationship between academic dishonesty and personal beliefs and values has been studied in many Western countries. However, the relationship between these variables have not been widely examined among higher education students in Malaysia. The purpose of this study is to determine the influence of personal beliefs and values, which consist of idealism, relativism and religious faith, on undergraduate students' academic dishonesty. A total of 2447 undergraduate students from four research universities in Malaysia participated in this study. The findings revealed that personal beliefs and values are significantly related to academic dishonesty. This study also indicated that idealism and religious faith are negatively related with academic dishonesty. Meanwhile, no significant relationship exists between relativism and academic dishonesty. Furthermore, the study found, after controlling for social desirability, idealism is the highest contributor to academic dishonesty. Based on the findings, it can be concluded that idealism and religious faith are important deterrents to academic dishonesty.